Green synthesis of silver nanoparticles aimed at improving theranostics - Vedelago, José Alberto (2018)
Nowadays, the combination of diagnosis and therapy, known as theranostics, is one of the keys for an optimal treatment for cancer diseases. Theranostics can be significantly improved by incorporating metallic nanoparticles that are specifically delivered and accumulated in cancerous tissue. In this context, precise knowledge about dosimetric effects in nanoparticle-infused tissues as well as the detection and processing of emerging radiation are extremely important issues. In the last years the first studies on theranostic nanomaterials in gel dosimetry have been presented but there is still a broad field of study to explore. Most of gel dosimetric materials are extremely sensible to modifications in their composition, the addition of enhancers, metallic or inorganic charges can alter their stability and dosimetric properties; therefore, thorough studies must be made before the incorporation of any type of modifier. In this work, the synthesis of metallic nanoparticles suitable for gel dosimetry for x-ray applications is presented. A green synthesis process of silver nanoparticles coated with porcine skin gelatin by thermal reduction of silver nitrate is presented. Nanoparticles were obtained and purified for their application in gel dosimetry. Also, nanoparticles size distribution, reaction yield and the preliminar application as theranostic agents were tested in Fricke gel dosimetry in the keV range. The obtained nanoparticles were successfully used in theranostic applications acting as fluorescent agents and dose enhancers in X-ray beam irradiation simultaneously.